Writing within simultaneity: A reflective progress report through letters from the Wits Writing Programme - Nichols, Pamela; Erasmus, Zimitri; Ntsepo, Nomonde; Mlahleki, Lerato; Mabalane, Keanu; Ngobeni, Khensani; Ckool, Lew Is (Stellenbosch Papers in Linguistics Plus, 2019)
Listening has long been understood as characteristic of writing centre practice, and as central to writing centre philosophy. This reflective progress report argues that such listening is also the generating culture of a university-wide writing programme of writing intensive courses, and that this culture will only be manifested and sustained if constantly modelled at all levels of the programme. In order to model what we teach, we need to build listening into the processes and structure of the programme as well as into the classrooms. Through letters from the invited co-authors of this paper, a snapshot is provided of the generative power of active listening in the teaching conversations between professor and writing fellows; lecturer, writing fellow and students; and writing fellows as a team as they create their lesson plan. Active listening is understood as a discipline of attentiveness to multiple and simultaneous meanings, and thus as a discipline which is necessary for complex thought and writing. Edward Said (2013) has described this attentiveness to simultaneity as key to a humanist critical literacy, which not only promotes engaged students and teachers but is also a political commitment to developing the citizen scholar. In the Wits Writing Programme, attentiveness to simultaneity represents a principle of teaching and of learning, an aim of writing, and a guiding value of the programme’s construction.